VARIATIONS IN ACCESSIBILITY OF ROUND WINDOW VIA POSTERIOR TYMPANOTOMY APPROACH IN COCHLEAR IMPLANT SURGERY - Mushahid, Uzair; Raza, Sayed Nusrat; Ali, Muhammad; Ahmed, Shoaib; Hakim, Abdul; Ahmed, Shakeel (Pakistan Armed Forces Medical Journal, 2021)
Objective: To apply the St Thomas’ Hospital (STH) classification of round window type, in a Pakistani pediatric population undergoing cochlear implantation, and rate the inter observer variability of applying this classification.Study Design: Cross sectional study.Place and Duration of Study: Combined Military Hospital Rawalpindi, from Apr 2019 to Dec 2020.Methodology: Patients were examined per-operatively by a panel of four surgeons after "optimal" posterior tympanotomy for round window variations, as per STH classification of approachability of RWM. The observations of the four surgeons were recorded and interobserver variation was assessed and analyzed.Results: A total of 100 patients were operated, 45 females and 55 males. Mean age was 3.8 years. There was minimal inter observer variability with regards to round window type and extent of "optimal" posterior tympanotomy. Three patients had type I, 76 had type IIA, 15 had type IIB and 6 patients had type III. Round window insertion/membranous cochleostomy was possible in 70 patients, whereas the rest require extended round window approach or bony cochleostomy.Conclusion: The STH classification is a useful predictor of route of CI electrode insertion and most patients can undergo RW insertion with confidence based on minimal variation between surgeons when applying the STH classification as well as when deciding the extent of surgical exposure.